Rancang Bangun Alat Uji Korosi Salt Spray Chamber dan Perhitungan Heat Transfer pada Chamber - Yosep Purnama; Wahyudi Wahyudi; Agus Subandi Harto (Journal of Mechanical Engineering and Mechatronics, 2017)
In designing and producing a salt spray chamber test apparatus for the required parameters to be standardized for the test method, the tool is designed and manufactured according to ASTM B117-09 standards, in addition to the standards mentioned, the design of this corrosion test apparatus also refers by studying ISO standards and JIS in the manufacture of such tools. By making this tool is expected to be able to test a specimen of a steel material. In addition to testing, heat transfer calculations and analysis in the chamber area are needed to determine the heat lost and the required power heater. From the result of spray salt collecting test obtained 1.5 ml salt solution in collecting cup with wide of  within 1 hour done in two positions, so for equalization of salt fog is in accordance with standard ASTM B117 collecting salt spray 1-2 ml / hr. The next parameter is that the temperature of the chamber must be maintained at 35°±2℃ from the temperature test results in accordance with ASTM B117 standard. From the test result of plate material JIS G 3141 SPCC (Steel Plate Cold Rolled Coiled) dimension 76 x 127 x 0.7 mm for 48 hours with test method. Neutral salt spray result from corrosion rate calculation got corrosion rate equal to 27.4665 mpy.